Archaeological Vector Graphics and SVG: A case study from Cricklade - Holly Wright (Internet Archaeology, 2006)
Currently, there are a variety of ways to make vector-based information available on the Web, but most are browser- and platform-dependent, proprietary, and unevenly supported (Laaker 2002, 13). Of the various solutions currently being explored by the greater Web community, one of the most promising is called Scalable Vector Graphics (SVG), which is part of the eXtensible Markup Language (XML). SVG was defined by a working group of the World Wide Web Consortium (W3C) and has subsequently become their official recommendation for representing vector graphics on the Web in XML (Eisenberg 2002, 6; Watt 2002, xviii). Because SVG is an XML application, it is freely available, not dependent on a particular browser or platform, and interoperable with other XML applications. While there is no guarantee that SVG will be widely adopted for rendering vector-based information on the Web, development and recommendation by the W3C generally carries a great deal of weight, especially as browser developers move towards less proprietary support of W3C standards. In addition, use of XML continues to grow, so XML-based solutions like SVG should be explored by those interested in presenting vector graphics on the Web (Harold and Means 2002, 3).